Designing Cases for Case-Based Immunology Teaching in Large Medical School Classes - Novack, Jeffrey P. (Frontiers in Immunology, 2020)
Abstract: Case-based, interactive sessions for small groups (in a large medical school class of 150 students) reinforce basic immunology concepts by including clinical scenarios that stimulate student learning and consolidate critical concepts. Careful design of cases (designing backwards from the key concepts) leads students through successively more complicated and linked group-work questions. This paper details why cases are effective learning tools, how to design an effective case, how to ask appropriate questions and how to help students apply basic immunology concepts to a case. Each group work session is facilitated and followed by a question and answer presentation by faculty, where student groups are directly asked to answer the questions and also challenged with “bonus questions” not presented with the original case. This allows students to “put together” immunology information into a “story” that they can tell and prevents student frustration by summarizing the results at the end of each case. Case design is carefully discussed including clinical relevancy and accuracy, how to write questions that do not give away the answers, how to emphasize mechanistic questions that allow students to “clinically explain as a physician” the immunological basis for the answers. Additionally, students better understand the role of immunity in both normal and disease states. A case-based approach promotes student learning by re-emphasizing basic concepts in the context of the case and promotes better students understanding of critical immunological concepts. Keywords: Immunology education, case-based learning, medical school education, team-based learning, key concepts, active learning, integrated curriculum.